Implementation of a buck boost converter in motor controller for a solar car - Mohd Azmi, Amat Manis (2010)
The transport needs of our ever growing and evolving society is becoming increasingly stringent and more demanding. In order to combat this, more efficient transportation vehicles need to be developed which are faster and cleaner. Solar Power is excellent energy source from the universe that can be converted into electricity using photovoltaic’s (PV) using the sunlight and less pollution which is also called renewable energy. The main problem from this energy is electricity produces by the PV is proportional with the sunlight radiation where the output voltage produces from PV can be increase or decrease depends on sunlight radiation. To solve this problem, buck boost converter is implemented to the system to maintain the output voltage at the desired value. When the PV get the maximum or minimum voltage from the sunlight, this converter will use to control the output voltage at the desired value to charging the battery. At the same time the PV collect a portion of the sun's energy and stores it into the batteries of the solar car that can be use in night day and cloudy condition. Pulse Width Modulation (PWM) is needed to control the switching frequency of semiconductor MOSFET in Buck Boost Converter circuit.